Global research progress on mining wastewater treatment: a bibliometric analysis. Issue 2 (4th May 2022) - Zahoor, Aqib; Mao, Guozhu; Jia, Xinming; Xiao, Xiao; Chen, Jian Lin
Abstract : Mining wastewater treatment (MWWT) methods have played a vital role in sustainable water management in recent years. Abstract : Mining wastewater treatment (MWWT) methods have played a vital role in sustainable water management in recent years. This bibliometric analysis summarized the scientific research improvement on MWWT and the assessment of future research. We employed bibliometric and social network analysis to quantitatively study 1542 research articles (published from 2001 to 2020) related to MWWT. The findings reveal that: (1) publications on MWWT have increased significantly since 2009, and researchers have intensively focused more on the application and optimization of current technologies such as membrane filtration systems, automatic variable filtration, advanced oxidation processes, and UV irradiation; (2) China and USA have the maximum number of research publications as well as are the centers in the international collaboration network, while Canada and European countries have produced a higher quality of papers; (3) through clusters of keywords and treatment technology analysis, the top three keywords are related to adsorption, oxidation, and activated sludge processes, corresponding to three types of mature wastewater treatment categories (physical, chemical, and biological); and (4) scientists have moved their focus to treatment technologies from the conventional to advanced ones for MWWT research. Finally, some problems and perspectives are presented, which might suggest current scientific hotspots and future research guidelines.